1995
DOI: 10.1044/jshr.3805.1143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age, Education, and Living Environment on Boston Naming Test Performance

Abstract: The 60-item Boston Naming Test (BNT; Kaplan, Goodglass, & Weintraub, 1983) was administered to 323 normal elderly subjects between the ages of 65 and 97. The combined effects of age, education, and living environment (institutionalized/independent living) on total test score was determined. These three variables accounted for 32% of the variance in BNT performance. Educational background accounted for the greatest proportion of the variance, followed by age and living environment. There was also a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
36
2
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 31 publications
11
36
2
2
Order By: Relevance
“…This study supports the findings of Welch et al (1996), Worrall et al (1995), Neils et al (1995), andHawkins et al (1993) studies that education level and BNT scores have a relationship. Welch et al, Worrall et a/.…”
Section: Education Levelsupporting
confidence: 94%
“…This study supports the findings of Welch et al (1996), Worrall et al (1995), Neils et al (1995), andHawkins et al (1993) studies that education level and BNT scores have a relationship. Welch et al, Worrall et a/.…”
Section: Education Levelsupporting
confidence: 94%
“…These findings were quite consistent with the previous research which has robustly found BNT scores to increase with higher educational levels (Elkadi et al, 2006;Fernandez-Blazquez et al, 2012;Neils et al, 1995). Therefore neuropsychologists in Latin America should use the education-adjusted norms generated for each country when administering the BNT in that country.…”
Section: Discussionsupporting
confidence: 81%
“…These age findings are similar to previous studies that have shown lower BNT scores in older adults (Fernandez-Blazquez et al, 2012), although as with the current study, age effects were generally smaller than education effects (Neils et al, 1995). On the other hand, one study did not find an effect of age on BNT performance (Aranciva et al, 2012).…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…The Boston Naming Test (BNT) (Kaplan et al 1983) is an instrument that is frequently used for the detection of these word-retrieval or naming di¬culties (Beele et al 1984, Worrall andBurtenshaw 1990). There is a considerable body of literature reporting the naming abilities of normal elderly as measured by the BNT (Albert et al 1988, Armstrong and Walker 1994, Au et al 1995, Farmer 1990, Goulet et al 1994, Kimbarrow et al 1996, LaBarge et al 1986, Mitrushina and Satz 1995, Neils et al 1995, Nicholas et al 1989, Nicholas et al 1985, Van Gorp et al 1986, Welch et al 1996, Worrall et al 1995. A review of this literature shows that reports of age-related performance of picture naming in normal elderly are inconsistent.…”
Section: Introductionmentioning
confidence: 95%